2022
DOI: 10.3389/fendo.2022.960551
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the mechanism by which skin macrophage dysfunction mediates chronic inflammatory injury in diabetic skin

Abstract: Macrophages, the main immune cells in the skin, form an innate immune barrier. Under physiological conditions, skin maintains immune barrier function through macrophage phagocytosis and antigen presentation. Parenchymal and stromal cell regeneration plays an important role in skin injury repair and uses macrophage plasticity to influence and stabilize the skin microenvironment. Diabetic skin lesions are the most common diabetes complication and are involved in the early pathophysiology of diabetic foot. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The importance of leukocyte dysregulation in the diabetic foot is underlined by the complexity of the role for the immune system in diabetes, DPN, and the formation of foot ulcers [ 9 , 22 , 40 44 ]. However, most transcriptomic analyses in diabetes thus far have focused on the pathophysiology of adipose tissue, sensory ganglia, or wounded/ulcerated skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of leukocyte dysregulation in the diabetic foot is underlined by the complexity of the role for the immune system in diabetes, DPN, and the formation of foot ulcers [ 9 , 22 , 40 44 ]. However, most transcriptomic analyses in diabetes thus far have focused on the pathophysiology of adipose tissue, sensory ganglia, or wounded/ulcerated skin.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the expression of APRIL by proinflammatory macrophages [ 56 ] and the expression of galectin by macrophages within atherosclerotic plaques [ 57 ] are consistent with the development of diabetes-related inflammation and cardiovascular disease in this model. Several publications implicate macrophages in the pathogenesis of diabetic neuropathy, with CD68 + macrophages detectable in sensory ganglia of patients with T2DM and DPN [ 10 ] and inflammatory pathways upregulated in macrophages in adipose tissue, foot ulcers, and circulating monocytes [ 12 , 13 , 22 , 40 , 58 ]. Here, we identified seven macrophage sub-clusters with a large degree of overlap in the defining genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, macrophages are still in an inflammation stage and cannot be transformed into a repair phenotype, leading to the inability to secrete the medium to promote tissue repair in the damaged tissues of diabetic patients. Moreover, the wound cannot turn to the proliferation stage, leading to chronic inflammation and nonhealing diabetic wounds 34,36,37 . To be more precise, a decrease in M2 macrophages and an increase in the M1/M2 ratio lead to a deficiency in growth factors, such as epidermal growth factor (EGF), fibroblast growth factor (FGF), platelet‐derived growth factor (PDGF), vascular endothelial growth factor (VEGF), anti‐inflammatory cytokines like interleukin 10 (IL‐10), transforming growth factor (TGF)‐α, and TGF‐β.…”
Section: Pathogenesis Of Dfumentioning
confidence: 99%
“…Moreover, the wound cannot turn to the proliferation stage, leading to chronic inflammation and nonhealing diabetic wounds. 34 , 36 , 37 To be more precise, a decrease in M2 macrophages and an increase in the M1/M2 ratio lead to a deficiency in growth factors, such as epidermal growth factor (EGF), fibroblast growth factor (FGF), platelet‐derived growth factor (PDGF), vascular endothelial growth factor (VEGF), anti‐inflammatory cytokines like interleukin 10 (IL‐10), transforming growth factor (TGF)‐α, and TGF‐β. These elements are essential for both the proliferation and remodeling phases.…”
Section: Pathogenesis Of Dfumentioning
confidence: 99%
“…Additionally, repeated therapies may increase the efficacy of combination therapy, and patients should be urged to seek treatment as soon as feasible. 63 To find the best technique for treating pathological scars, a network meta-analysis compared and ranked the effectiveness of laser and IPL treatments. It was shown that the combination of IPL and CO 2 laser has the greatest likelihood of being the most successful intervention.…”
Section: Combination Therapymentioning
confidence: 99%